Enzymes in human milk - Dallas, David C. (Nestle Nutr Inst Workshop Ser, 2017)
Milk proteins are a complex and diverse source of biological activities. Beyond their function intact, milk proteins also act as carriers of encrypted functional sequences that when released as peptides exert biological functions, including antimicrobial and immunomodulatory, which could contribute to the infant’s competitive success. Research has now revealed that the release of these functional peptides begins within the mammary gland itself. A complex array of proteases produced in mother’s milk have been shown to be active in the milk, releasing these peptides. Moreover, our recent research demonstrates that these milk proteases continue to digest milk proteins within the infant’s stomach, possibly even to a larger extent than the infant’s own proteases. As the neonate has relatively low digestive capacity, the activity of milk proteases in the infant may provide important assistance to digesting milk proteins. The coordinated release of these encrypted sequences is accomplished by selective proteolytic action provided by an array of native milk proteases and infant-produced enzymes. The task for scientists is now to discover the selective advantages of this protein-protease based peptide release system.